2023
DOI: 10.1002/mdc3.13656
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Disorders and Movement Disorders—A Systematic Review

Abstract: Background There is overlap between movement disorders and neuroendocrine abnormalities. Objectives and methods To provide a systematic review on the association of thyroid dysfunction and movement disorders. Thyroid physiological function and classical thyroid disorders highlighting typical and atypical manifestations including movement disorders, as well as diagnostic procedures, and treatments are discussed. Results Hypothyroidism may be associated with hypokinetic and hyperkinetic disorders. There is debat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 115 publications
(255 reference statements)
0
4
0
Order By: Relevance
“…MCT8-deficient BBB-Chips showed significantly lower permeability for T3, which is a thyroid precursor. The results of this study confirmed the necessity of MCT8 protein for T3 transport across BBB, and given that loss of thyroid hormone-binding proteins increases the vulnerability of striatal neurons in Huntington's Disease [11], the model confirmed the contribution of MCT8 deficiency to the disorder. Similarly, Pediaditakis et al 2021 showed that abnormal accumulation of alpha-synuclein aggregates led to phosphorylation of αSyn localized in the endothelial cells in the vascular channel and therefore BBB damage in Parkinson's Disease [12]; Shin et al 2019 showed that in Alzheimer's Disease there is increased BBB permeability induced by reduced expression of tight junction and adherens proteins [13].…”
Section: Applications Of Bbb Chipssupporting
confidence: 73%
“…MCT8-deficient BBB-Chips showed significantly lower permeability for T3, which is a thyroid precursor. The results of this study confirmed the necessity of MCT8 protein for T3 transport across BBB, and given that loss of thyroid hormone-binding proteins increases the vulnerability of striatal neurons in Huntington's Disease [11], the model confirmed the contribution of MCT8 deficiency to the disorder. Similarly, Pediaditakis et al 2021 showed that abnormal accumulation of alpha-synuclein aggregates led to phosphorylation of αSyn localized in the endothelial cells in the vascular channel and therefore BBB damage in Parkinson's Disease [12]; Shin et al 2019 showed that in Alzheimer's Disease there is increased BBB permeability induced by reduced expression of tight junction and adherens proteins [13].…”
Section: Applications Of Bbb Chipssupporting
confidence: 73%
“…1 Since then, there have been various case reports of the condition, but it still remains a rare occurrence. 2 In our country, this is the first reported case in literature.…”
Section: What Is the Diagnosis?mentioning
confidence: 70%
“…1 Thyroid involvement may manifest as congenital hypothyroidism 2 or compensated hypothyroidism in childhood or even adulthood. 6 Our patient had well-controlled hypothyroidism with onset in early childhood and motor delay. This presentation contrasted with that of the patient with the same variant reported by Li et al, 2 who had congenital hypothyroidism and marked motor and language developmental delay.…”
mentioning
confidence: 64%